Tracking plastics in the Mediterranean: 2D Lagrangian model. Issue 1 (April 2018) - Liubartseva, S.; Coppini, G.; Lecci, R.; Clementi, E.
Abstract: Drift of floating debris is studied with a 2D Lagrangian model with stochastic beaching and sedimentation of plastics. An ensemble of >10 10 virtual particles is tracked from anthropogenic sources (coastal human populations, rivers, shipping lanes) to environmental destinations (sea surface, coastlines, seabed). Daily analyses of ocean currents and waves provided by CMEMS at a horizontal resolution of 1/16° are used to force the plastics. High spatio-temporal variability in sea-surface plastic concentrations without any stable long-term accumulations is found. Substantial accumulation of plastics is detected on coastlines and the sea bottom. The most contaminated areas are in the Cilician subbasin, Catalan Sea, and near the Po River Delta. Also, highly polluted local patches in the vicinity of sources with limited circulation are identified. An inverse problem solution, used to quantify the origins of plastics, shows that plastic pollution of every Mediterranean country is caused primarily by its own terrestrial sources. Highlights: 2D Lagrangian tracking of plastics by sea surface currents and Stokes drift Monte Carlo technique for beaching and sedimentation of plastics Substantial accumulation of plastics on coastlines and the sea bottom Absence of any long-term accumulation of plastics at the sea surface Inverse source identification stresses the importance of ICZM at a national level.